(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Diospyros malabarica (Desr.) Kostel (DMDK) plant is abundantly grown, and various parts are traditionally used for treating diarrhea, wound, cancer, diabetes, ulcer, and renal diseases. However, its medicinal importance is not assessed. Further, it was observed that there is no pharmacological standard established on fruits of DMDK. Therefore, the present study investigates the nephroprotective activity of DMDK fruits against the gentamicin (GEN) induced nephrotoxicity model. Ethanolic extract of fruits of DMDK (EEFDMDK) was screened for its nephroprotective activity against GEN (100 mg/kg i. p.) induced nephrotoxicity in rats by standard method. The protective property of EEFDMDK was assessed by measuring the body weight (BW) of animals before and after experiments and calculating a change in body weight (CIBW) of animals, the weight of kidney (WK), urine output, estimating biochemical parameters, and histopathological observations of a kidney. Our data showed that GEN administration resulted in significantly increased levels of biochemical parameters. Pretreatment with EEFDMDK normalized the GEN-induced increased levels of biochemical parameters. We also observed that EEFDMDK significantly protect the rat kidneys from GEN-induced histopathological changes. Similarly, EEFDMDK restored BW reduction of animals and prevented an increase in WK of animals. The possible mechanism underlying this effect is mediated collectively through the presence of polyphenols like flavonoids, tannins, and the diuretic effect of the DMDK.